TECHNIQUE OF CLAVICULA RADIOGRAPHY EXAMINATION IN CASES OF SINISTRA CLAVICULA FRACTURE IN RADIOLOGY INSTALLATION OF EFARINA ETAHAM BERASTAGI HOSPITAL KARO DISTRICT 2020 - Firdasari, Firdasari; Costinot, Arnaud; Fajar, Ibnu; Yunardi, Yunardi; Wahyuni Tarigan, Sri (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
The clavicle or collarbone is a long bone that serves as a support between the scapula and the sternum (breastbone). There are two Clavicula, namely the right and left. The clavicle is the only long bone in the body that is positioned horizontally. Together with the shoulder blades, it makes up the shoulder girdle. These are bones that are commonly touched, and in people who have less fat in this area, their location is very obvious, as they give rise to bumps in the skin. He received it from the Latin “Clavicula” which means little key, because the bone rotates along its axis like a key. The clavicle is the most commonly fractured bone. The bone can easily be broken by an impact to the shoulder from the force of a fall with an outstretched arm or a direct blow.